2022
DOI: 10.3390/metabo12121247
|View full text |Cite
|
Sign up to set email alerts
|

Modulatory Effect of Gut Microbiota on the Gut-Brain, Gut-Bone Axes, and the Impact of Cannabinoids

Abstract: The gut microbiome is a collection of microorganisms and parasites in the gastrointestinal tract. Many factors can affect this community’s composition, such as age, sex, diet, medications, and environmental triggers. The relationship between the human host and the gut microbiota is crucial for the organism’s survival and development, whereas the disruption of this relationship can lead to various inflammatory diseases. Cannabidiol (CBD) and tetrahydrocannabinol (THC) are used to treat muscle spasticity associa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 241 publications
0
22
0
Order By: Relevance
“…The brainstem has a higher quantity of the peptide hormone GLP-1 than other parts of the CNS. Its physiological impacts include glucose metabolism, brain function, and neurological protection (Ibrahim et al, 2022). Several organs, such as the kidney, lung, heart, and CNS, have been shown to have GLP-1 receptors.…”
Section: Alzheimer's Disease (Ad)mentioning
confidence: 99%
“…The brainstem has a higher quantity of the peptide hormone GLP-1 than other parts of the CNS. Its physiological impacts include glucose metabolism, brain function, and neurological protection (Ibrahim et al, 2022). Several organs, such as the kidney, lung, heart, and CNS, have been shown to have GLP-1 receptors.…”
Section: Alzheimer's Disease (Ad)mentioning
confidence: 99%
“…212 Other microbial metabolites, including amino acidderived metabolites, may also cross the placenta, with potential effects on fetal development. 213,214 Further, there is growing evidence for a wide variety of other metabolites, produced through the action of microbiota on dietary nutrients, which may affect host health, including amino acids, 215 soy-derived isoflavones, [216][217][218][219] cannabinoids, 220 and phenolic acids, 221 in addition to a large number of pharmacological and host metabolites that may be modulated by microbiota. 110,[222][223][224][225]…”
Section: Microbial Metabolismmentioning
confidence: 99%
“…Synergistic studies of polymyxin B and CBD co-therapy demonstrated strong antibacterial activities against Acinetobacter baumannii ATCC 19606 and other gram-negative bacteria ( Klebsiella pneumoniae and Pseudomonas aeruginosa ) ( 9 ). Some non-pathogenic bacteria such as gut microbiota is an integral aspect of human health, and while food and antibiotic consumption does affects the gut microbiota and sometimes provides an easy pathway for infections arising from foodborne pathogens ( 10 ), CBD has been demonstrated to boost enzyme activities of these gut bacteria ( 11 , 12 ).…”
Section: Introductionmentioning
confidence: 99%